Scaffolding leadership dispositions for being radically truthful in the civitas dei and the civitas mundi: An imaginative educative ethical-justice praxis - Dames, Gordon E (Stellenbosch Theological Journal, 2020)
Societies across the globe need a new kind of leadership education characterised with a disposition for radical truth-telling. This ideal should go beyond generalised and familiarised ethical leadership formation. Contemporary leaders should become truth tellers and truth seekers for justice. Attaining such a disposition calls us towards an imaginative ethical-educative praxis for justice. Scaffolding leadership-ethical-presences towards being human may proof indispensable. The rediscovery of a vocation for an ethically re-envisioned educational revolution is called for.